Anticancer potential of delphinidin and its derivatives: therapeutic and mechanistic insights - Iqbal, Shabnoor; Omara, Timothy; Kahwa, Ivan; Khan, Usman Mir (Medicinal Chemistry Research, 2024)
Anthocyanins are water-soluble naturally occurring ﬂavonoids present in fruits, ﬂowers, leaves, and roots of fruit plants and vegetables. One of the important anthocyanidin components of red wine and berries is delphinidin (DP). This review provides an update on the potential of DP in cancer therapy, with a further understanding of the mechanisms involved. Delphinidin has been shown to elicit inhibitory effects on catabolizing enzymes of human granulocytes and parasites, TNF-induced COX-2 expression in mouse epidermal cells, and reduce oxidative stress. It also inhibited anchorage-independent growth and caused cell death in breast cancer cell lines. Delphinidin increased Nrf2 expression, increased HO-1 production, and promoted mRNA expression of mitochondrial biogenesis-related factors. Further, DP has anti-proliferative and pro-apoptotic effects in various cancer cell lines such as lung, breast, and ovarian cancer cells. The mTOR-related pathway is the most important signaling pathway in the activation of autophagy, and DP has been shown to exert its cytotoxic effects on cancer cell lines via activating protein kinases. Among DP derivatives, delphinidin-3-O-glucoside has the best anticancer activity because it is easily absorbed. However, the metabolism of DP and its bioavailability in biological systems need to be explored to fully understand its beneﬁts.
Keywords: Pro-inﬂammatory genes; Target sites; Antiproliferative effect; Anthocyanins